2016
DOI: 10.5858/arpa.2016-0459-sa
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Cellular Rejection and Antibody-Mediated Rejection on Lung Transplant Biopsies: A Perspective From Members of the Pulmonary Pathology Society

Abstract: Context.— The diagnosis and grading of acute cellular and antibody-mediated rejection (AMR) in lung allograft biopsies is important because rejection can lead to acute graft dysfunction and/or failure and may contribute to chronic graft failure. While acute cellular rejection is well defined histologically, no reproducible specific features of AMR are currently identified. Therefore, a combination of clinical features, serology, histopathology, and immunologic findings is suggested for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 46 publications
0
62
0
2
Order By: Relevance
“…The presence and role of C4d, a complement split product, in lung allograft is unclear, in part because the reproducibility of C4d results has been problematic . In addition, C4d deposition can be seen in any other process associated with complement activation, highlighting its lack of specificity for DSA‐related processes. In our study, we found no difference in C4d staining in DSA positive or negative groups supporting the consensus from earlier reports …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence and role of C4d, a complement split product, in lung allograft is unclear, in part because the reproducibility of C4d results has been problematic . In addition, C4d deposition can be seen in any other process associated with complement activation, highlighting its lack of specificity for DSA‐related processes. In our study, we found no difference in C4d staining in DSA positive or negative groups supporting the consensus from earlier reports …”
Section: Discussionmentioning
confidence: 99%
“…In addition, C4d deposition can be seen in any other process associated with complement activation, highlighting its lack of specificity for DSA‐related processes. In our study, we found no difference in C4d staining in DSA positive or negative groups supporting the consensus from earlier reports …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-invasive tests like pulmonary function testing and chest imaging are useful indicators for potential complications, but have no discriminatory value between ACR and infection [9]. For these reasons, transbronchial biopsies (TBB) remain the gold standard for the diagnosis of ACR [10]. However, TBB are invasive and bear potential risks such as pneumothorax or bleeding [11,12].…”
Section: Introductionmentioning
confidence: 99%